The last resort : taking the Mississippi cure - Watkins, Norma (Willie Morris books in memoir and biography., 2011)
Raised under the racial segregation that kept her family's southern country hotel afloat, Norma Watkins grows up listening at doors, trying to penetrate the secrets and silences of the black help and of her parents' marriage. Groomed to be an ornament to white patriarchy, she sees herself failing at the ideal of becoming a southern lady. When a civil rights lawyer offers love and escape, does a good southern lady dare leave her home state and closed society behind? The Last Resort conveys at once the idyllic charm and the impossible compromises of a lost way of life.